Preferences for patient-centered care among cancer survivors 5 years post-diagnosis. Issue 8 (August 2020) - Chan, Caryn Mei Hsien; Blanch-Hartigan, Danielle; Taib, Nur Aishah; Wee, Lei Hum; Krupat, Edward; Meyer, Fremonta
Highlights: This study offers insight into preferences for patient-centered care among cancer survivors. Higher cancer health literacy was associated with greater survivor preference for patient-centered care. Findings underscore the need to take into consideration cancer health literacy levels which may influence care preferences. Abstract: Objective: Our primary objective was to identify predictors associated with preferences for patient-centered care among cancer survivors and the association between cancer health literacy and patient-centered care preferences. Methods: Cross sectional analyses of N = 345 adult cancer survivors (5 years post cancer diagnosis) attending follow-ups at University Malaya Medical Centre, Malaysia. Face-to face-interviews were conducted using the 30-item Cancer Health Literacy Test and the Patient-Practitioner Orientation Scale to determine preference for patient-centered care. Results: Cancer survivors' preference for patient-centered care was associated with a higher cancer health literacy score, higher educational level, being employed, breast cancer diagnosis, and not desiring psychological support [ F (14, 327) = 11.25, p < 0.001, R 2  = 0.325]. Conclusion: Findings from this study provide insights into preferences for patient-centered care among cancer survivors during receipt of follow-up care, which remains an understudied phase of cancer care delivery. Practice implications: Efforts are needed to ensure different preferences for care are taken into account particularly in the setting of variable cancer health literacy.